Update of Meat Standards Australia and the cuts based grading scheme for beef and sheepmeat - Sarah P.F. Bonny; Rachel A. O'Reilly; David W. Pethick; Graham E. Gardner; Jean-François Hocquette; Liselotte Pannier (Journal of Integrative Agriculture)
Changing markets and evolving consumer demand present new challenges for the beef and sheep industries. In response, the industry has been investing in innovations to deliver new products and management systems to consumers. One such innovation is the Meat Standards Australia (MSA) system. This system is a Total Quality Management System, aimed at delivering an eating quality guarantee to consumers, and through this adding value to the entire supply chain. At present, it is well developed for beef and still evolving for sheepmeat. MSA has identified Critical Control Points (CCPs) in the production, pre-slaughter, processing and value-adding aspects of the supply chain that impact on consumer palatability through the large-scale taste testing of meat by untrained consumers. These CCPs are used as either (1) mandatory criteria determining eligibility for grading, and (2) inputs in a model predicting the palatability of individual combinations of muscle and different cooking methods. Through the prediction of palatability, MSA increases consumer satisfaction and is used to provide assurance for branded products and new marketing innovations in Australia and internationally. This has added significant value to the Australian beef industry, with several retail examples demonstrating consumer willingness to pay more for premium quality beef and sheepmeat products based on the MSA grading scores. This price differential at retail allows the value of the carcass to be calculated based on the eating quality as well as the volume produced, thereby delivering a financial reward for farmers producing high quality carcasses. The continuous quality scale of MSA allows producers to realise the financial gain of incremental improvements in quality, as well as the precise economic weights associated with traits such as marbling, ossification score, or breed. The use of MSA in this fashion has underpinned a new and innovative supply chain where the pricing is transparent and allows producers to make informed decisions to modify both quality and yield traits. To date, the MSA system for beef has proved to be effective in predicting beef palatability not only in Australia but also in many other countries (France, Poland, Ireland, Northern Ireland, Japan, South Korea, New-Zealand, the USA and South Africa). In Europe, results of the ProSafeBeef and ProOptiBeef projects as well as other national projects demonstrate the potential to develop an MSA-like international grading system for the supply chain in the EU, despite the diverse cultures and complex beef production systems within the member states. International testing in lamb has only just begun and preliminary results are discussed here.